URGENSI PEMBAHARUAN UNDANG-UNDANG PENYIARAN MENGENAI PERIZINAN PENYIARAN BERBASIS INTERNET DI INDONESIA - Tina Maylani, (Magister Hukum Universitas Semarang, 2023)
The purpose of this research is to examine the urgency regarding the renewal of the Broadcasting Law regarding internet-based broadcasting licensing in Indonesia. The development of the internet which continues to grow has an impact on the broadcasting industry by shifting from conventional broadcasting to digital broadcasting via the internet. Because internet broadcasting is currently not subject to Law concerning Broadcasting and is included in the category of electronic system operators subject to concerning Telecommunications, this creates a problem, namely specifically regarding licensing. The existence of regulatory disharmony regarding conventional broadcasting licensing and broadcasting using the internet has resulted in different treatment, resulting in losses for conventional broadcasting operators. Therefore broadcasting regulations have an urgency to be updated considering the development of the internet which continues to encourage new innovations and is expected to provide equality in law in the licensing process between conventional broadcasting operators and broadcasting using the internet. This study uses a normative juridical method and a comparative approach. The results of this study indicate that it is necessary to update the Broadcasting Law which regulates internet-based broadcasting, especially in terms of internet-based broadcasting licensing procedures which can refer to rules that have been implemented in other countries.